1992
DOI: 10.1139/v92-337
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric enrichment in binary solvent mixtures. The intramolecular hydrogen bond in N-alkyl-substituted o-nitroanilines. Substituent effects

Abstract: In this work we report solvatochromism studies on o-nitroaniline and several N-alkyl-o-nitroaniline derivatives used as solutes in solvent mixtures of an "inert" nonpolar cosolvent, cyclohexane, and THF as a solvent with hydrogen bond acceptor ability. These studies allowed us to establish the competition between inter-and intramolecular hydrogen bond in solutes. This was done by comparing the magnitude of the local inhomogeneity induced by the solute-in-solvent mixture, that is, "preferential solvation," usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…8 Solvatochromic studies have been carried out using o-nitroaniline and severa l N -a lkyl-o-nitroaniline derivatives as solutes in solvent mixtures of an inert nonpolar cosolvent, cyclohexane, and tetrahydrofuran as a solvent with hydrogen bond acceptor ability. 9 Characterization of methanol/water and acetonitrile/water m ixtures has been carried out by a combination of solvatochromic and m ultivariate curve resolution methods. 10 In these studies, evidence has been found for form ation of mixed solvent complexes that play a role in the obser ved solvatochromic properties.…”
Section: Physical Basis Of So Lvatochrom Ismmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Solvatochromic studies have been carried out using o-nitroaniline and severa l N -a lkyl-o-nitroaniline derivatives as solutes in solvent mixtures of an inert nonpolar cosolvent, cyclohexane, and tetrahydrofuran as a solvent with hydrogen bond acceptor ability. 9 Characterization of methanol/water and acetonitrile/water m ixtures has been carried out by a combination of solvatochromic and m ultivariate curve resolution methods. 10 In these studies, evidence has been found for form ation of mixed solvent complexes that play a role in the obser ved solvatochromic properties.…”
Section: Physical Basis Of So Lvatochrom Ismmentioning
confidence: 99%
“…Over the past few years, the solvatoch ro m ic com p arison m etho d, which is based on the effect of solvent polarity on the electronic excitation energy of indicator dyes, has been used to successfully characterize various solvents. This method has also been applied to the characterization of systems such as mixed solvents, [3][4][5][6][7][8][9][10] dry solid surfaces such as silica, 11,12 silicalite and zeolites, 13 and alumina, 14 and also 'wetted' or 'solvated' solid surfaces, such as liquid ch ro m atog ra p hic stationar y bonded phases. 12,[15][16][17][18][19][20][21][22][23][24][25][26] This method has also been extended to supercritical uids [27][28][29][30][31] and to organized m edia such as cyclodextrins and micelles.…”
Section: Introductionmentioning
confidence: 99%
“…The solute surrounds itself preferably by the component in the mixture, which leads to the more negative Gibbs energy of solvation, as expected. 49 The observation that the solvent shell has a composition other than the macroscopic ratio is termed selective or preferential solvation. 33,35 Thus, QB seems to detect more GY molecules in its solvent shell than that corresponding to the bulk composition, and probably as a consequence the GY:DMF mixture is not ideal as it was previously demonstrated by other authors.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…Thus, the solvatochromism of o-nitroaniline and N-alkyl-o-nitroaniline probes was studied in solvent mixtures involving an 'inert' non-polar cosolvent (CHX) and an HBA solvent (THF) [122,123].…”
Section: Selection Of Fluorescence Probesmentioning
confidence: 99%